Herbivore abundance, site fidelity and grazing rates on temperate reefs inside and outside marine reserves - Ferguson, A.; Harvey, Euan; Knott, N. (Elsevier, 2016)
A key objective of marine reserves is to maintain ecological processes important to the functioning of marine ecosystems. Grazing by tropical herbivores contributes to maintaining resilient coral reefs and marine reserves are critical in conserving herbivores and the functional role they provide. Less is known, however, about the effects of marine reserves on herbivorous fish and their role on temperate reefs. This study evaluated the potential for marine reserves to enhance grazing by herbivores on temperate reefs in Jervis Bay Marine Park, Australia. First, the movement patterns of a dominant grazer, luderick Girella tricuspidata, were determined using acoustic telemetry to assess the potential effects of marine reserves on G. tricuspidata. Second, the size and abundance of G. tricuspidata and other grazers (rock blackfish Girella elevata and silver drummer Kyphosus sydneyanus) was quantified on shallow subtidal reefs inside and outside marine reserves using a diver operated stereo-video system. Finally, grazing rates were quantified inside and outside marine reserves using video cameras. Luderick G. tricuspidata exhibited strong site fidelity on shallow subtidal reefs and was significantly larger and more abundant within marine reserves. Rock blackfish G. elevata was significantly more abundant in one of four marine reserves, although showed no difference in size between zones. Silver drummer K. sydneyanus was significantly larger in marine reserves, although not significantly more abundant. On shallow subtidal reefs, G. tricuspidata was the dominant grazer compared to other girellids and kyphosids, accounting for >. 97% of total algal bites (predominantly on algal turfs). Grazing rates were higher on average within marine reserves (although not significantly higher) and there was a positive correlation between the relative abundance of G. tricuspidata and number of algal bites, indicating grazing intensity increased with abundance. The findings in this study demonstrate the clear potential for greater grazing by herbivores within temperate marine reserves. This study also suggests that exploitation of targeted herbivores on temperate reefs is significant and marine reserves can reduce this impact and allow it to be measured via reference areas.